Haptoglobin polymorphism correlated with coronary artery disease - Alegranci, Pamela [UNESP] (2009)
Introduction: Haptoglobin polymorphism has been correlated with disease and some studies have associated the Hp(2) allele with susceptibility to or protection against certain infectious (pulmonary tuberculosis, HIV) and non-infectious (diabetes, coronary artery disease, obesity) diseases. The aim of this study was to verify possible correlations of haptoglobin genotypes and subtypes by comparing coronary artery disease (CAD) patients with blood donors.Material and methods: Haptoglobin genotypes and subtypes were analyzed by DNA amplification with the Dral restriction enzyme, in 125 CAD patients diagnosed by coronary angiography, and 125 blood donors as matched healthy controls.Results: The distribution of haptoglobin genotypes was similar in the groups, without significant statistical differences (p = 0.643). The Hp(2)/Hp(2) genotype was more frequent in both the CAD group and blood donors followed by Hp(2)/Hp(1) and Hp(1)/Hp(1). The allele frequency of Hp2 was higher than Hp(1) in the groups. The results showed a significant difference (p = 0.002) between the groups regarding haptoglobin subtypes; Hp(2FS)/Hp(2FS) was prevalent in both groups with the least frequent subtype being Hp(2FF)/Hp(2FF) for CAD patients and Hp(1F)/Hp(1S) among blood donors. There was a statistically significant difference (p = 0.027) between the frequencies of the commonest allele subtype, Hp(2FS), and the least common, Hp(2FF).Conclusions: Unlike blood donors, the Hp(2FF)/Hp(2FF) haptoglobin subtype was the least frequent among CAD patients, which may implicate this subtype in the development of CAD, a disease with a high mortality rate which consequently reduces the proportion of these individuals in populations.